2023
DOI: 10.3390/antiox12030769
|View full text |Cite
|
Sign up to set email alerts
|

Recent Perspective of Lactobacillus in Reducing Oxidative Stress to Prevent Disease

Abstract: During oxidative stress, an important factor in the development of many diseases, cellular oxidative and antioxidant activities are imbalanced due to various internal and external factors such as inflammation or diet. The administration of probiotic Lactobacillus strains has been shown to confer a range of antibacterial, anti-inflammatory, antioxidant, and immunomodulatory effects in the host. This review focuses on the potential role of oxidative stress in inflammatory bowel diseases (IBD), cancer, and liver-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…In fact, the potential association between Lactobacillus and longevity and health was proposed over a century ago (Mackowiak 2013 ). Recent studies have not only reported the important roles of Lactobacillus in gut homeostasis, immune regulation, inflammation, oxidative stress, and nervous system regulation, but also confirmed its significant potential in extending lifespan (Grompone et al 2012 ; Kumaree et al 2023 ; Zhao et al 2023 ). However, the specific mechanisms of Lactobacillus in delaying aging and maintaining healthy aging are still unclear.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, the potential association between Lactobacillus and longevity and health was proposed over a century ago (Mackowiak 2013 ). Recent studies have not only reported the important roles of Lactobacillus in gut homeostasis, immune regulation, inflammation, oxidative stress, and nervous system regulation, but also confirmed its significant potential in extending lifespan (Grompone et al 2012 ; Kumaree et al 2023 ; Zhao et al 2023 ). However, the specific mechanisms of Lactobacillus in delaying aging and maintaining healthy aging are still unclear.…”
Section: Discussionmentioning
confidence: 92%
“…The results of this study were consistent with the above study ( Hassan et al, 2020 ), L. plantarum ATCC14917 can reverse the changes in the structure of the gut microbiota induced by the HFD, notably the major bacterial phylum. In recent years, many studies have shown that probiotics can regulate intestinal flora to prevent intestinal flora imbalance, improve intestinal barrier function, reduce oxidative stress and inflammation, and improve lipid metabolism and NAFLD ( Cao et al, 2022 ; Hu et al, 2022 ; Arellano-García et al, 2023 ; Shin et al, 2023 ; Wang et al, 2023 ; Zhao et al, 2023 ). In addition, there are several studies on the effects of different probiotics on improving NAFLD in clinical trials ( Arellano-García et al, 2022 ; Noormohammadi et al, 2023 ; Zhou et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These polysaccharides act by downregulating the expression of MAPK mRNA and upregulating PTEN (Asoudeh-Fard et al, 2017). Research on L. lactis strains has revealed their capacity to secrete IL-10 and INF-β, as well as express antioxidants that mitigate the generation of reactive oxygen species (ROS) and reduce colonic damage in animal models (Zhao et al, 2023).…”
Section: Probiotics In Cancer Prevention and Treatmentmentioning
confidence: 99%